PENGARUH PRILAKU PRODUKTIF DAN TOTAL QUALITY MANAGEMENT TERHADAP KINERJA KARYAWAN (Studi pada TV MU) - Saptono, Asrul; Sutanto, Aftoni; Hidayat, Abdul Choliq (Universitas Indo Global Mandiri Palembang, 2020)
Several factors are used to measure employee performance, namely employee internal factors and external factors that are following an employee's personal needs. One internal factor used to measure employee performance is one of the individual productivity factors and one of the external factors of employees who implement Total Quality Management (TQM) in the company where they work. This study aims to test the success and TQM on employee performance. The object of this research is in the Muhammadiyah Television company in Jakarta and Yogyakarta. Through examining the perception of 30 employees. The method of analysis uses multiple regression.The results of this study explain that the Productive Behavior Variable has a significant effect on Employee Performance with a significance value of 0.041 less than the Alpha value of 0.05; thus, the first hypothesis accepted. TQM variable is significant on company performance with a significance value of 0,000 smaller than the Alpha value of 0.05. Therefore the second hypothesis is accepted. Hypothesis test results three explain together Productive behavior variables, and TQM significantly influences Employee Performance with a significance value of 0,000 smaller than the Alpha value of 0.05. Thus the null hypothesis is accepted.Â Keywords : Productive behavior, TQM, Performance.